BTLA agonist attenuates Th17-driven inflammation in a mouse model of steroid-resistant asthma - Quach, Christine; Li, Xin; Shafiei-Jahani, Pedram; Li, Meng; Shen, Stephen; Helou, Doumet Georges; Hurrell, Benjamin P.; Soroosh, Pejman; Akbari, Omid (Frontiers in Immunology, 2025)
IntroductionSteroid-resistant asthma does not respond adequately to corticosteroid treatment. The underlying mechanisms driving corticosteroid resistance remain poorly understood, partly due to the absence of suitable animal models. Identifying the immunomodulatory pathways and mechanisms driving steroid resistance is crucial for developing effective therapies.MethodsIn this study, we screened 58 murine strains exposed to house dust mite and identified that the BXD75 strain exhibited neutrophil-skewed, steroid-resistant asthma and elevated Th17 cells. RNA sequencing of lung CD4+ T cells from BXD75 was performed to identify immunomodulatory pathways involved in steroid-resistance. The effects of BTLA agonist treatment were assessed on airway hyperreactivity and lung inflammation.ResultsTranscriptomic analysis revealed increased HVEM expression and decreased BTLA expression, both critical immune regulators associated with stimulatory and inhibitory signaling, respectively. These T cells demonstrated enhanced inflammatory signaling through both canonical and non-canonical NF-κB pathways. BTLA agonist treatment in vivo reduced airway hyperreactivity and lung inflammation, while ex vivo treatment of Th17 cells induced inhibitory signaling via SHP-1, suppressed NF-κB signaling, reduced cell numbers, and lowered IL-17 levels.DiscussionOur findings establish BXD75 mice as a model for steroid-resistant asthma and demonstrate that BTLA agonism attenuates airway hyperreactivity and lung inflammation, highlighting it as a potential therapeutic strategy.